Comparative Evaluation of Efficacy and Safety of the Diode Laser (980 nm) and Sclerotherapy in the Treatment of Oral Vascular Malformations. (5th September 2022) - Shivhare, Peeyush; Haidry, Naqoosh; Sah, Neha; Kumar, Ajay; Gupta, Abhishek; Singh, Ankur; Penumatcha, Mohan Raju; Subramanyam, Shalini
Abstract : Background . Vascular malformations are structural abnormalities which are formed by progressively enlarging aberrant and ecstatic vessels without endothelial cell proliferation and composed of the type of vessel involved, i.e., capillary, veins, and arteriovenous. Treatment of vascular malformations may involve many techniques like sclerotherapy, embolization, surgical resection, cryotherapy, laser treatment, or medical therapy. This observational prospective study is aimed at evaluating and comparing the effects and efficacy of diode laser and sclerotherapy in the treatment of oral vascular malformation. Materials and Methods . 40 patients presenting with oral vascular malformation were included in the present study. The patients were divided equally (20 in each) into two groups, i.e., the laser group and sclerotherapy group. Sclerotherapy was performed with 3% sodium tetradecyl sulfate while the laser group was treated with diode laser 980 nm with transmucosal thermophotocoagulation. The patients were assessed for the response, remission, and side effects. The results obtained were tabulated and compared with the chi-square test. Results . Side effects were found significantly lesser in the laser group compared to the sclerotherapy group (p < 0.05 ). Statistically significant difference was seen for postoperative pain between two groups. The laser group had mild to moderate pain compared to severe pain in the sclerotherapy group. Recurrence was observed more in the laser group compared to the sclerotherapy group. Conclusions . Laser and sclerotherapy with 3% sodium tetradecyl sulfate both are effective in the treatment of vascular malformations. Diode laser seems to be better than sclerotherapy given lesser side effects and comfort to the patients while sclerotherapy seems to be better in respect to recurrences.